Affective Circuitry Alterations in Patients with Trigeminal Neuralgia - Hayes, Dave J.; Chen, David Q.; Zhong, Jidan; Lin, Ariel; Behan, Brendan; Walker, Matthew; Hodaie, Mojgan (Frontiers in Neuroanatomy, 2017)
Trigeminal neuralgia (TN) is a severe chronic neuropathic facial pain disorder. Affect-related behavioural and structural brain changes have been noted across chronic pain disorders, but have not been well-studied in TN. We examined the potential impact of TN (37 patients: 23 with right-sided TN, 14 with left-sided TN), compared to age- and sex-matched healthy controls, on three major white matter tracts responsible for carrying affect-related signals – i.e. cingulum, fornix, and medial forebrain bundle. Diffusion magnetic resonance imaging (dMRI), deterministic mutli-tensor tractography for tract modelling, and a model-driven region-of-interest approach was used. We also used volumetric grey matter analysis on key targets of these pathways (i.e. hippocampus, cingulate cortex subregions, nucleus accumbens and ventral diencephalon). Hypotheses included: 1) successful modelling of tracts; 2) altered white matter microstructure of the cingulum and medial forebrain bundle (via changes in dMRI metrics such as fractional anisotropy, and mean, axial and radial diffusivities) compared to controls; 3) no alterations in the control region of the fornix; 4) corresponding decreases in grey matter volumes. Results showed 1) all 325 tracts were successfully modelled, although 11 were partially complete; 2) The cingulum and medial forebrain bundle (MFB) were altered in those with TN, with dMRI metric changes in the middle (p=0.001) and posterior cingulum (p<0.0001), and the MFB near the ventral tegmental area (MFB-VTA) (p=0.001). The posterior cingulum and MFB-VTA also showed unilateral differences between right- and left-sided TN patients; 3) No differences were noted at any fornix subdivision; 4) decreased volumes were noted for the hippocampus, posterior cingulate, nucleus accumbens, and ventral diencephalon. Together, these results support the notion of selectively altered affective circuits in patients with TN, which may be related to the experience of negative affect and the increased comorbidity of mood and anxiety disorders in this population.